ok well here is the problem..
and here is my answer,
im not seeing where i went wrong, used partial fractions to break it down, i figured out A to be 1/3 and B to be 2/3...
any help would be appreciated, thanks in advance
ok well here is the problem..
and here is my answer,
im not seeing where i went wrong, used partial fractions to break it down, i figured out A to be 1/3 and B to be 2/3...
any help would be appreciated, thanks in advance
Your partial fractions are wrong.
It should be A/s + B/(s + 3) = 1/(s^2 + 3s)
[A(s + 3) + Bs]/[s(s + 3)] = 1/[s(s + 3)]
A(s + 3) + Bs = 1
As + 3A + Bs = 1
(A + B)s + 3A = 0s + 1
A + B = 0 and 3A = 1
A = 1/3 and B = -1/3.
So 1/(s^2 + 3s) = 1/(3s) - 1/[3(s + 3)]. Now find the inverse Laplace transform.